Observation of the System Earth from Space - CHAMP, GRACE, GOCE and future missions GEOTECHNOLOGIEN Science Report No. 20 - Flechtner, Frank; Sneeuw, Nico.; Schuh, Wolf-Dieter.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Significant advances in the scientific use of space based data were achieved in three joint interdisciplinary projects based on data of the satellite missions CHAMP, GRACE and GOCE within the R&D program GEOTECHNOLOGIEN. It was possible to explore and monitor changes related to the Earth$1 (Bs surface, the boundary layer between atmosphere and solid earth, and the oceans and ice shields. This boundary layer is our habitat and therefore is in the focus of our interests. The Earth$1 (Bs surface is subject to anthropogenetic changes, to changes driven by the Sun, Moon and planets, and by changes caused by processes in the Earth system. The state parameters and their changes are best monitored from space. The theme (3z(BObservation of the System Earth from Space(3y (Boffers comprehensive insights into a broad range of research topics relevant to society including geodesy, oceanography, atmospheric science (from meteorology to climatology), hydrology and glaciology.s
Part I. 1. Lotse CHAMP-GRACE: An interdisciplinary research project for earth observation from space -- 2. Improvement in GPS orbit determination at GFZ -- 3. Using accelerometer data as observations -- 4. GFZ RL05 - an improved time -series of monthly GRACE gravity field solution -- 5. GRACE gravity modeling using the integrated approach -- 6. Comparison of daily GRACE solutions to GPS station height movements -- 7. Identification and reduction of satellite-induced signals is GRACE accelerometer data -- 8. Reprocessing and application of GPS radio occultation data from CHAMP and GRACE -- Part II. 9. Real data analysis GOCE (REAL GOCE) -- 10. GOCE gravity gradients: reprocessed gradients and spherical harmonic analyses -- 11. GOCE gravity gradients : combination with GRACE and satellite altimetry -- 12. Incorporating topographic-isostatic information into GOCE gravity gradient processing -- 13. Global gravity fields from different GOCE orbit products -- 14. Adjustment of digital filters for decorrelation of GOCE SGG data -- 15. Stochastic modeling of GOCE gravitational tensor invariants -- 16. Cross-overs assess quality of GOCE gradients -- 17. Consistency of GOCE geoid information with in situ ocean and atmospheric data, tested by ocean state estimation -- 18. Regional validation and combination of GOCE gravity field models and terrestrial data -- 19. Height system unification based on GOCE gravity field models - benefits and challenges -- 20. EIGEN-6C - a high resolution global gravity combination model including GOCE data.
Keywords: Geography; Physical geography; Remote sensing; Astronautics; Earth Sciences; Geophysics/Geodesy.; Aerospace Technology and Astronautics; Remote Sensing/Photogrammetry.